Assessing the Impact of Electronic Word of Mouth on Muslim Millennials’ Travel Intentions: Evidence from Muslim-Friendly Tourism in Lombok - Nuzulia, Nuzulia; Achsania Hendratm (El-Qish: Journal of Islamic Economics, 2025)
Tourism is a vital global industry contributing to foreign exchange, regional development, and employment. However, the COVID-19 pandemic in early 2020 led to a drastic decline in tourist visits and expenditures. This study examines the factors influencing Muslim millennials’ intentions to visit Muslim-friendly destinations in Lombok, focusing on electronic word of mouth (e-WOM), Islamic tourism motivation, pandemic risk perception, and attitude toward destinations. Quantitative data were collected from 210 Muslim millennial respondents and analyzed with Partial Least Squares Structural Equation Modeling (SEM-PLS) via SmartPLS. The results indicate that e-WOM, Islamic tourism motivation, and attitude toward destinations significantly and positively affect visit intentions, while pandemic risk perception does not significantly impact. These findings suggest that psychological and informational factors, especially those distributed digitally, have a more substantial influence than health-related concerns. The study provides practical implications for halal tourism destination managers in optimizing e-WOM and digital marketing strategies, while maintaining post-pandemic health protocols to enhance tourist confidence. This research contributes to the post-pandemic halal tourism literature by integrating psychological and contextual variables in understanding the travel behavior of Muslim millennials.